Reflections on Vedic wisdom - Baruah, Ratul Bujar; Atreya, Kamal Lochan; Deka, Pranabjyoti
Contributed research papers presented at three day National Seminar on "Vedas, the Source of Oriental Knowledge System" organized by Kumar Bhaskar Varma Sanskrit and Ancient Studies University, Nalbari, Assam on 9th to 11th February, 2017).